Investigation of interaction between extreme waves and a moored FPSO using FNPT and CFD solvers. (15th June 2020) - Hu, Zheng Zheng; Yan, Shiqiang; Greaves, Deborah; Mai, Tri; Raby, Alison; Ma, Qingwei
Abstract: To assess the survivability of marine structures, numerical tools that can predict the interaction between extreme waves and structures are needed. Considering the significant nonlinearity associated with the problem, fully nonlinear models, including the fully nonlinear potential theory (FNPT) and general viscous flow theory based on the Navier-Stokes equation (NS) and Continuity equation, are necessary for a reliable prediction. Both methods have relatively higher computational cost compared to the linear or second order wave theories, which are popular in routine design practices. Although the FNPT model generally requires less computational efforts compared to the NS model, its theoretical assumption, i.e. the flow is incompressible, irrotational and inviscid, invalidates its applications to those problems with significant viscous effects and/or breaking waves. It is, therefore, necessary to conduct a comparative study on the accuracy of the FNPT in various problems to quantify its range of application. In this paper, both the Quasi Arbitrary Lagrangian Eulerian Finite Element (QALE-FEM) method based on the FNPT model and the open source Reynolds Average Navier-Stoke (RANS) based code, OpenFOAM, are used to predict the interaction between extreme waves and a moored Floating Production Storage and Offloading (FPSO) model. The extreme waves are generated using the NewWave theory and different wave steepnesses are used. The results, including the wave runup, pressure and force on the FPSO, are compared with the corresponding experimental data obtained from the ocean basin at the COAST Laboratory, University of Plymouth. Satisfactory agreement between the numerical predictions and the experimental measurements are observed. It is also concluded that the differences between the QALE-FEM results and the OpenFOAM results are mainly caused by the effectiveness of the wave generation in the corresponding simulations; the viscous effects may be considerable in the rotational motion of the FPSO when subjected to extreme waves. Highlights: A numerical comparative study on extreme wave interaction with moored FPSO using FNPT (QALE-FEM) and CFD solvers (OpenFOAM). New sets of experimental data for interaction between extreme waves and a moored FPSO. Investigations on the viscous effects associated with the FPSO in extreme wave conditions. Effect of the wave generation on overall accuracy of wave runup and motion responses of the floating structures.